2021
DOI: 10.3390/ijms22147588
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of Rat Skeletal Muscle Is Associated with Increased SIRT1/Akt/mTOR/S6 and Suppressed Sestrin2/SIRT3/FOXO1 Levels

Abstract: Despite the intensive investigation of the molecular mechanism of skeletal muscle hypertrophy, the underlying signaling processes are not completely understood. Therefore, we used an overload model, in which the main synergist muscles (gastrocnemius, soleus) of the plantaris muscle were surgically removed, to cause a significant overload in the remaining plantaris muscle of 8-month-old Wistar male rats. SIRT1-associated pro-anabolic, pro-catabolic molecular signaling pathways, NAD and H2S levels of this overlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Sirtuins, particularly SIRT1 and SIRT6, play significant roles in this process (Table 3 ). Research indicates that overload-induced hypertrophy in skeletal muscles of rats is linked to increased expression of SIRT1 but decreased SIRT3 level, which is implicated in mitochondrial degradation 122 , 123 . SIRT1 also regulates myonuclear domain size in skeletal muscle fibers, where overexpression decreases domain size while inactivation increases it, with no significant impact on muscle force 124 .…”
Section: Sirtuins In Skeletal Muscle: Exploring Their Role In Develop...mentioning
confidence: 99%
“…Sirtuins, particularly SIRT1 and SIRT6, play significant roles in this process (Table 3 ). Research indicates that overload-induced hypertrophy in skeletal muscles of rats is linked to increased expression of SIRT1 but decreased SIRT3 level, which is implicated in mitochondrial degradation 122 , 123 . SIRT1 also regulates myonuclear domain size in skeletal muscle fibers, where overexpression decreases domain size while inactivation increases it, with no significant impact on muscle force 124 .…”
Section: Sirtuins In Skeletal Muscle: Exploring Their Role In Develop...mentioning
confidence: 99%
“…Liu et al found that iris reduced gluconeogenesis by downregulating PI3K/Akt/Foxo1-mediated PEPCK and G6Pase compared with the model group, thereby improving glucose homeostasis in STZ/HFD mice [ 122 ]. Foxo1 also contributes to the regulation of glucose in skeletal muscle [ 130 ]. Under the condition of chronic starvation, increased foxo1 expression in muscle binds to the promoter of pyruvate dehydrogenase kinase-4 gene, resulting in the conversion of pyruvate to acetyl-CoA and accelerating glucose consumption [ 131 ].…”
Section: The Role Of the Liver In Regulating Glucose Metabolismmentioning
confidence: 99%
“…One mechanism through which SIRT1 improves T2D symptoms is by deacetylating and thus activating FoxO1 in adipocytes and increasing FoxO1’s interaction with its coactivator CCAAT/enhancer-binding protein α (C/EBPα) to upregulate the transcription of the insulin-sensitizing hormone adiponectin ( 59 ). However, SIRT1 can also act to mitigate T2D by enhancing AKT-mediated FoxO1 inactivation in tissues like liver and skeletal muscle ( 60 , 61 ). Therefore, increased SIRT1 can improve T2D symptoms by either activating or inactivation FoxO1.…”
Section: Foxo1 Structure Function and Regulationmentioning
confidence: 99%
“…Further studies suggest that both AKT and SIRT1 regulate FoxO1’s effects on muscle mass and GLUT4 ( 107 ). Elevated SIRT1 during cardiac or skeletal muscle hypertrophy has been associated with increased AKT levels and activity and decreased FoxO1 ( 61 , 107 109 ). For example, Gombos et al.…”
Section: Foxo1 and T2d – Skeletal Musclementioning
confidence: 99%